Features of setting up and solving the design and verification tasks on the example calculation of rectification of a binary mixture - M. K. Zakharov; Yu. A. Pisarenko (Тонкие химические технологии, 2015)
Various variants of setting up the rectification simulation task (verification task and design task) were considered with the distillation of binary mixtures as an example. Based on the analysis of degrees of freedom the interrelation between the character of the simulation problem and the types of operating parameters was determined. It is shown that, when dealing with the verification task, it is necessary to exclude a dramatic difference in the properties of the initial mixture and the liquid phase located on a feed plate.